2007
DOI: 10.1302/0301-620x.89b1.17485
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6, procalcitonin and TNF-α

Abstract: This prospective study evaluates the role of new laboratory markers in the diagnosis of deep implant infection in 78 patients (41 men and 37 women) with a revision total knee or hip replacement. The mean age at the time of operation was 64.0 years (19 to 90). Intra-operative cultures showed that 21 patients had a septic and 57 an aseptic total joint replacement. The white blood cell count, the erythrocyte sedimentation rate and levels of C-reactive protein, interleukin-6, procalcitonin and tumour necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(88 citation statements)
references
References 19 publications
2
77
1
4
Order By: Relevance
“…Bottner et al [24] measured serum levels of several biomarkers including: PCT, interleukin (IL)-6, tumor necrosis factor (TNF)-α, ESR, and CRP in 78 patients undergoing revision arthroplasty for PJI. The sensitivity of CRP and IL-6 were the highest (95%) when the levels were greater than 3.2 mg/ dL and 12 pg/mL, respectively.…”
Section: Serum Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Bottner et al [24] measured serum levels of several biomarkers including: PCT, interleukin (IL)-6, tumor necrosis factor (TNF)-α, ESR, and CRP in 78 patients undergoing revision arthroplasty for PJI. The sensitivity of CRP and IL-6 were the highest (95%) when the levels were greater than 3.2 mg/ dL and 12 pg/mL, respectively.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…IL-6 is another serum marker that has gained attention for diagnosing PJI. IL-6 is secreted by different immune cells and triggers the excretion of CRP; therefore, it is believed that the IL-6 levels rise much faster than CRP and has been reported to be a sensitive marker for diagnosing PJI, however it also lacks specificity [24,28]. (p-6) Wirtz et al [29] advocated the role of IL-6, and in their study authors showed that IL-6 is a better indicator for postoperative inflammatory response than CRP in patients undergoing TJA.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…Farklı çalışmalar-da duyarlığı %73-91, özgüllüğü %81-86 arasında değiştiği bildirilmiş ve 13.5 mg/dl üzerinde anlamlı kabul edilmesi önerilmiştir (13,15). Bottner ve arkadaşları (14), çalışma-larında eşik değer olarak 3.2 mg/dl aldıklarında özgüllü-ğün %96'ya çıktığını bulmuşlardır. Ayrıca CRP ve ESH'nin birlikte değerlendirilmesi, infeksiyon nedeniyle revizyon yapılan hastalarda infeksiyonu belirlemede tek tek değer-lendirmeye göre daha değerli bulunmuştur (14).…”
Section: Tanıda Laboratuvarunclassified
“…Bottner ve arkadaşları (14), çalışma-larında eşik değer olarak 3.2 mg/dl aldıklarında özgüllü-ğün %96'ya çıktığını bulmuşlardır. Ayrıca CRP ve ESH'nin birlikte değerlendirilmesi, infeksiyon nedeniyle revizyon yapılan hastalarda infeksiyonu belirlemede tek tek değer-lendirmeye göre daha değerli bulunmuştur (14). Diz protez infeksiyonu olan ve sinovyal sıvıda %80'den fazla nötro-fil saptanan hastaların ESH ve CRP değerleri birlikte değerlendirildiğinde duyarlılığı %87, özgüllüğü %90, pozitif prediktif değeri %93, negatif prediktif değeri %82 olarak saptanmıştır (p<0.0001) (16).…”
Section: Tanıda Laboratuvarunclassified
See 1 more Smart Citation